Predictors of readiness to participate in training program among civil servants in Nigeria and intervening roles of intention towards training and gender - Nnamdi, Ogbodoakum (2020)
Training opportunities in any organisation, especially in the public sector is a powerful indication to the employees that, their services are valued and appreciated. Despite the plethora of evaluative measures to uncover the growing trends of training ineffectiveness in many organisations, very few positive outcomes have been achieved. The main problem is that, significant number of studies were devoted to training evaluation, with little reference to employee readiness to participate in such training programme. Following the literature reviews, it was discovered that, no study has been conducted in Nigeria on the predictors of civil servants’ readiness to participate in training and interviewing role of intention towards training and gender using the theory of theory of planned behaviour and decomposed theory of planned behaviour. Seven constructs were identified and used in the study (attitude towards training, peer influence, superior influence, training self-efficacy, facilitating conditions, intention towards training and readiness to participate). Data were obtained from civil servants who have participated in a training program from three government organisations in Nigeria: Supreme court, Federal judicial service commission and Federal civil service commission. Pilot study was conducted with a sample of 30 respondents in other to assess the reliability of the instrument, which was fully satisfied. The research instrument contains 68 items (61, validated and 7 self-developed), which was assessed on a 7-point Likert scale with a sample size of 255 (valid respondents) 64%, out of a possible 400 distributed copies. Structural equation modelling was applied to analyse the data, after painstaking data examination in terms of normality, validity, reliability and multicollinearity. The following results were found (1) attitude towards training and Intention towards training have significant direct effect on readiness to participate. (2) intention towards training partially mediated the effect of attitude towards training on readiness to participate. (3) intention towards training fully mediated the effect of peer influence, superior influence, training self-efficacy and facilitating The research instrument contains 68 items (61, validated and 7 self-developed), which was assessed on a 7-point Likert scale with a sample size of 255 (valid respondents) 64%, out of a possible 400 distributed copies. Structural equation modelling was applied to analyse the data, after painstaking data examination in terms of normality, validity, reliability and multicollinearity. The following results were found (1) attitude towards training and Intention towards training have significant direct effect on readiness to participate. (2) intention towards training partially mediated the effect of attitude towards training on readiness to participate. (3) intention towards training fully mediated the effect of peer influence, superior influence, training self-efficacy and facilitating condition on readiness to participate (4) there was a statistically significant effect of gender on readiness to participate, which is suggestive that female civil servants have higher readiness to participate in training compared to male civil servants. The following conclusions were drawn from the study. Firstly, attitude towards training and intention towards were the most significant determinants for readiness to participate in training within the civil service. Although, peer influence, superior influence, training selfefficacy and facilitating condition are important in achieving civil servants’ readiness to participate in training, its effect will depend on employee intention towards training. It is suggested that training in the civil service should be targeted, egalitarian and resulted oriented in other to achieve optimum performance among the staff members. The study has the following implications in the context of human resource development. First, the study re-enforced the central role of behavioural intention as the most important determinant for actual behaviour (readiness to participate). Second, there is an urgent need to integrate individual and organisational factors in managing employee readiness to participate, especially in a rule-based hierarchical civil service. Finally, it was observed that, the central determinant of strong intention is motivation, hence policy makers should priorities staff motivation by adopting fair and just policies in other to ensure high readiness to participate in training and other applicable organizational interventions in the civil service.